1988
DOI: 10.1007/bf00116866
|View full text |Cite
|
Sign up to set email alerts
|

Lower critical field and magnetization of strong-coupling, type II superconductors in the dirty limit

Abstract: Usadel's dirty-limit version of the Gorkov-Eilenberger theory including strongcoupling effects is used to calculate the lower critical field of superconducting alloys. The results of the (rigorous) numerical study, which is valid for all temperatures and Ginzburg-Landau parameters K, are compared with experiments and with the existing weak-coupling theory. One achieves agreement with the bulk of the experimental results only if K is properly adjusted. In addition, it is shown that a circular-cell approximation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…For superconductors with arbitrary purity the FLL was computed from microscopic theory in the quasiclassical formulation by Eilenberger (1968), which expresses the free energy in terms of energy-integrated Green functions; see also Usadel (1970) for the limit of impure superconductors (with numerical solutions by Watts-Tobin et al 1974 andRammer 1988) and the carefull discussion of this quasiclassical approximation by Serene and Rainer (1983). The computations by , Kramer and Pesch (1974), Watts-Tobin et al (1974), Rammer et al (1987), and Rammer (1988) used a circular cell method, which approximates the hexagonal Wigner-Seitz cell of the triangular FLL by a circle, and the periodic solutions by rotationally symmetric ones with zero slope at the circular boundary (Ihle 1971). Improved computations account for the periodicity of the FLL (Klein 1987, Rammer 1991a, see also the calculation of the density of states near B c2 by Pesch (1975) and recent work by Golubov and Hartmann (1994).…”
Section: Ideal Flux-line Lattice From Microscopic Bcs Theorymentioning
confidence: 99%
“…For superconductors with arbitrary purity the FLL was computed from microscopic theory in the quasiclassical formulation by Eilenberger (1968), which expresses the free energy in terms of energy-integrated Green functions; see also Usadel (1970) for the limit of impure superconductors (with numerical solutions by Watts-Tobin et al 1974 andRammer 1988) and the carefull discussion of this quasiclassical approximation by Serene and Rainer (1983). The computations by , Kramer and Pesch (1974), Watts-Tobin et al (1974), Rammer et al (1987), and Rammer (1988) used a circular cell method, which approximates the hexagonal Wigner-Seitz cell of the triangular FLL by a circle, and the periodic solutions by rotationally symmetric ones with zero slope at the circular boundary (Ihle 1971). Improved computations account for the periodicity of the FLL (Klein 1987, Rammer 1991a, see also the calculation of the density of states near B c2 by Pesch (1975) and recent work by Golubov and Hartmann (1994).…”
Section: Ideal Flux-line Lattice From Microscopic Bcs Theorymentioning
confidence: 99%
“…In Refs. [9][10][11][12][13], the GL equations and the equations of the microscopic theory of superconductivity were solved numerically in the framework of circular cell approaches and it was shown that this approximation not only yields good results at low induction but also at H ∼ H c2 . A similar approach was used in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…To describe the vortex structure at arbitrary fields we employ the circular cell approximation [19][20][21][22]. Within this approach the unit cell of the hexagonal vortex lattice hosting a single vortex is replaced by a circular cell with the centre at the point of superconducting phase singularity.…”
Section: Modelmentioning
confidence: 99%
“…The approach presented in Sec. II reduces to the single-band model, if λ 12 = λ 21 = 0 and D 1,2 = D. For λ 11 > λ 22 , it corresponds to the description of the independent stronger-superconductivity band. Fig.…”
Section: A Single-band Limitmentioning
confidence: 99%